(untitled) (Research, Society and Development, 2020)
The outsourcing of services has been widely used in public organizations, which tends to expand after the authorization of outsourcing in finalistic areas. From then on, it is up to the institutions to designate the servant that will act as contract inspectors and will monitor contractual execution. The main objective of the research was to understand the dynamics of the performance of contract inspectors, the structure and the institutional support received to fulfill this function. A case study was carried out in two federal educational institutions and, based on the data analysis, the existing weaknesses in the process of designation and training of contract inspectors were identified, as well as it was possible to elucidate the greatest difficulties and challenges during the performance of assignments. The main difficulties identified were: the need for further training; task overload; lack of adequate time to exercise the function; task overlays; constraints arising from interaction with other sectors or between the inspection team; lack of interest or even absence of the manager during the monitoring of the contract; and difficulty in monitoring the execution of the contracted service. It was found that institutions need to improve working conditions, offering inspectors better support and organizational structure.